FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PAJAK PADA UKM DAN USAHA INFORMAL DI INDONESIA - Ahmad Rizani (Prosiding Seminar Nasional Indonesia, 2025)
This study aims to identify and analyse the factors that influence tax compliance in Small and Medium Enterprises (SMEs) and informal businesses in Indonesia through a systematic literature review. Tax compliance in this sector is a major challenge in optimising state revenue, given the significant contribution of SMEs to the national economy. The study focuses on two main groups of factors, namely internal factors, which include tax knowledge, taxpayer attitudes, economic capacity, and financial management, as well as external factors, which include tax regulations, administrative convenience, fiscal incentives, the role of tax officials, and digital technology support. The results of the study show that a synergistic combination of internal and external factors greatly determines the level of tax compliance among SMEs and informal businesses. Therefore, an integrated approach to taxation policy and education is essential to encourage sustainable and inclusive compliance.